Robert Ellis. Ernst Toller and German Society: Intellectuals as Leaders and Critics 1914-1939. Madison: Fairleigh Dickinson UP, 2013. - Margy J Gerber (Studies in 20th & 21st Century Literature, 2017)
Review of Robert Ellis. Ernst Toller and German Society: Intellectuals as Leaders and Critics 1914-1939. Madison: Fairleigh Dickinson UP, 2013.
Keywords: Ernst Toller; Intellectuals as Leaders; Weimar Republic; communalism